Strengthening the Euro Area : The Role of National Structural Reforms in Building Resilience - Bluedorn, John.; Aiyar, Shekhar; Duval, Romain; Furceri, Davide (Washington, D.C. : International Monetary Fund, 2019)
Cross-country differences in economic resilience-in an economy's ability to withstand and adjust to shocks-remain significant in the euro area. In part, the differences reflect the lack of a national nominal exchange rate as a mechanism to adjust to shocks. The IMF staff has argued that union-wide architectural changes such as the banking union, the capital markets union, and a central fiscal capacity can help foster greater international risk sharing. Yet even these changes cannot insure against all shocks. National policies thus have a vital role to play. This IMF staff discussion note analyzes how national structural policies can help euro area countries better deal with economic shocks. Using a mix of empirical and modeling approaches, the note finds that growth-enhancing reforms to labor and product market regulations, tailored to country-specific circumstances, would help individual euro area economies weather adverse shocks. Higher-quality insolvency regimes are associated with more efficient factor reallocation following a shock. The note also finds that structural and cyclical policies interact. Greater rigidities make economies more fragile, putting a higher burden on fiscal policy. This is especially true for members of a monetary union. Countries should build fiscal space in good times and tackle rigidities, reducing their need for countercyclical policies in bad times while making countercyclical policies more effective when deployed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet